Duplex Ultrasound Evaluation of Portal Vein Diameter as a Predictor of Esophageal Varices: A Cross-Sectional Study - Imran , Ahmed; Akter, Nargis; Afroz , Rozina; Sultana , Masuma; Nasrin, Shamima; Haque, Shahara (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Portal hypertension is directly related to esophageal varices, a common side effect of liver cirrhosis. Given the high mortality rate of life-threatening variceal hemorrhage, early detection is essential. Despite being the gold standard for diagnosing varices, endoscopy's invasiveness and scarcity underscore the need for trustworthy non-invasive substitutes. One method that has shown promise in the prediction of esophageal varices is duplex ultrasound, specifically the measurement of portal vein diameter. Objective: The purpose of this study was to evaluate the diagnostic precision of portal vein diameter, as determined by duplex ultrasound, in identifying esophageal varices in patients with cirrhosis. Methods: A cross-sectional study with 58 liver cirrhosis patients was carried out in the department of Radiology & Imaging, Dhaka Medical College, Dhaka, from July 2021 to June 2023. Both outpatient department or indoor patients were included. Portal vein diameter was measured using duplex ultrasound; a value of >13 mm is thought to be a predictive threshold for esophageal varices. Statistical analyses of the result were obtained by using window-based Microsoft Excel and Statistical Package for Social Sciences (SPSS-24). Results: Excellent diagnostic accuracy was shown by portal vein diameter >13 mm, with a sensitivity of 94.87%, specificity of 73.68%, PPV of 88.10%, NPV of 87.50%, and overall accuracy of 87.93%. 95% CI: 0.827–0.993, p < 0.001, and the AUC was 0.874. Of the 39 patients who had varices confirmed by endoscopy, 37 were properly identified, and two were overlooked. Fourteen of the 19 patients without varices were correctly ruled out, while 5 were false positives. Conclusion: A very useful non-invasive marker for esophageal varices, portal vein diameter as determined by duplex ultrasound holds great promise in settings with limited resources. J Com Med Col Teachers’ Asso July 2025; 29(2): 89-93